Conception Management Class : Problems and Solutions - Salabi, Ahmad (Jurnal Tarbiyah : Jurnal Ilmiah Kependidikan, 2016)
The success of student learning in the classroom, in addition to the factors affecting learning, influenced by factors of class management. Management classes include child discipline management, socio-emotional climate of the classroom, classroom social climate, and the physical condition of class. Classroom management aims to create a classroom climate conducive to ease the childs learning. For that, they need the skills of teachers in classroom management is good. Many of the problems challenging classes derived from the class itself. Therefore required a format appropriate solutions, systematic and well-planned.